Contralateral axillary metastasis: a diagnostic and therapeutic clinical dilemma. Issue 2 (9th February 2021) - Abdulla, Hussain Adnan; AlQaseer, Asma; Bukamal, Zain; Alrayes, Amal
Abstract : We report a 61-year-old woman with primary right breast cancer and metastatic lymphadenopathy in the contralateral axilla. This case represents a clinical dilemma because primary breast cancer, occult contralateral breast cancer and extra-mammary primary lesion can all be the source of the contralateral axillary metastasis. The patient underwent bilateral modified radical mastectomy. Immunohistochemistry revealed that the right breast was positive for estrogen receptor (ER) and progesterone receptor (PR), but negative for human epidermal growth factor receptor-2 (HER2). In contrast, the right and left axillary lymph nodes were positive for ER, but negative for PR and HER2. There was no evidence of occult primary cancers or extra-mammary tumours.